Occupational exposure to solvents and risk of lymphoma subtypes: results from the Epilymph case–control study. Issue 5 (6th May 2010) - Cocco, P; t'Mannetje, A; Fadda, D; Melis, M; Becker, N; de Sanjosé, S; Foretova, L; Mareckova, J; Staines, A; Kleefeld, S; Maynadié, M; Nieters, A; et al.
Abstract : Background: Several studies have suggested an association between occupational exposure to solvents and lymphoma risk. However, findings are inconsistent and the role of specific chemicals is not known. Objective: To investigate the role of occupational exposure to organic solvents in the aetiology of B-cell non-Hodgkin's lymphoma (B-NHL) and its major subtypes, as well as Hodgkin's lymphoma and T-cell lymphoma. Methods: 2348 lymphoma cases and 2462 controls participated in a case–control study in six European countries. A subset of cases were reviewed by a panel of pathologists to ensure diagnostic consistency. Exposure to solvents was assessed by industrial hygienists and occupational experts based on a detailed occupational questionnaire. Results: Risk of follicular lymphoma significantly increased with three independent metrics of exposure to benzene, toluene and xylene (BTX) (combined p=4×10 −7 ) and to styrene (p=1×10 −5 ), and chronic lymphocytic leukaemia (CLL) risk increased with exposure to solvents overall (p=4×10 −6 ), BTX (p=5×10 −5 ), gasoline (p=8×10 −5 ) and other solvents (p=2×10 −6 ). Risk of B-NHL for ever exposure to solvents was not elevated (OR=1.1, 95% CI 1.0 to 1.3), and that for CLL and follicular lymphoma was 1.3 (95% CI 1.1 to 1.6) and 1.3 (95% CI 1.0 to 1.7), respectively. Exposure to benzene accounted, at least partially, for the association observed with CLL risk. Hodgkin's lymphoma and T-cell lymphoma did not show an association with solvent exposure. Conclusion: This analysis of a large European dataset confirms a role of occupational exposure to solvents in the aetiology of B-NHL, and particularly, CLL. It is suggested that benzene is most likely to be implicated, but we cannot exclude the possibility of a role for other solvents in relation to other lymphoma subtypes, such as follicular lymphoma. No association with risk of T-cell lymphoma and Hodgkin's lymphoma was shown.